A bibliometric analysis of metal-based catalysts for efficient hydrogen production - Saeid, Mohammed Faraj; Abdulkadir, B. A.; Mohammad Ismail, .; Herma Dina, Setiabudi (John Wiley and Sons Inc., 2025)
This study investigates global research trends on the catalytic performance of metal-based catalysts for enhanced hydrogen production over the past 89 years (1935–2024) through a comprehensive bibliometric analysis. The research addresses the evolution of metal-based catalysts in hydrogen production and highlights the most prominent contributors and driving trends. The study analyzed 32,987 peer-reviewed studies identified through Scopus database. The search was conducted from September 1, 1935, to July 20, 2024, utilizing keywords such as “(TITLE-ABS-KEY ((“Ru” OR “Ni” OR “Fe” OR “Co” OR “Mo” OR “Pt” OR “Pd” OR “Cr” OR “metal catalysts*”) AND (“hydrogen production*” OR “H2 production*” OR “hydrogen generation*” OR “H2 generation*”))).” The analysis covered various aspects, such as countries, authors’ affiliations, prominent journals, research areas, and key terms driving discussions in the field. It also noted that researchers with fewer publications may have been overlooked. Bibliometric parameters, including publication counts, citations, total link strength (TLS), and collaboration networks, were examined. Results indicate a steady rise in publications, with significant growth observed from 2000 onwards. The most recent period (2019–2024) alone accounted for 55.6% of the total publications, with a notable 26.5% growth from 2021 to 2022. China leads in both publication volume and TLS, followed by the United States and the United Kingdom. The International Journal of Hydrogen Energy (IJHE) emerged as the top journal with 4653 relevant articles. The analysis reveals a shift in focus from early studies on iron and platinum to a more recent emphasis on nickel-based catalysts and hydrogen evolution reactions (HER). These findings highlight several challenges, including the need to improve catalyst efficiency, address scalability issues, and develop more sustainable catalytic materials. Future research should focus on advancing catalyst design, optimizing reaction conditions, and enhancing catalytic stability for large-scale hydrogen production.